Immobilized RGD concentration and Proteolytic Degradation Synergistically Enhance Vascular Sprouting within Hydrogel Scaffolds of Varying Modulus - He, Yusheng J. (J Biomater Sci Polym Ed, 2019)
Insufficient vascularization limits the volume and complexity of biomaterials-based tissue engineering approaches. The formation of new blood vessels (neovascularization) is regulated by a complex interplay of cellular interactions with biochemical and biophysical signals provided by the extracellular matrix (ECM) which necessitates the development of biomaterial approaches that enable systematic modulation in matrix properties. Poly(ethylene) glycol-based hydrogel scaffolds were engineered with a range of decoupled and combined variations in integrin-binding peptide (RGD) ligand concentration, elastic modulus and proteolytic degradation rate using free-radical polymerization chemistry. The modularity of this system enabled a full factorial experimental design to simultaneously investigate the individual and interaction effects of these matrix cues on vascular sprout formation in 3D culture. Enhancements in scaffold proteolytic degradation rate promoted significant increases in vascular sprout length and junction number while increases in modulus significantly and negatively impacted vascular sprouting. We also observed that individual variations in immobilized RGD concentration did not significantly impact 3D vascular sprouting. Our findings revealed a previously unidentified and optimized combination whereby increases in both immobilized RGD concentration and proteolytic degradation rate resulted in significant and synergistic enhancements in 3D vascular spouting. The above-mentioned findings would have been challenging to uncover using one-factor-at-time experimental analyses.